On the funeral texts of Hipolit Pikalski OP (1827–1887) - Borkowski, Igor (Requiem, 2025)
This paper presents a collection of funeral eulogies prepared and delivered by the Dominican friar Hipolit Pikalski from 1852 to 1860. The analysis includes a characterisation of the archival collection and examines the content of the texts in terms of the funeral narrative and pastoral content. The main part of the work, however, focuses on the biographer’s description of the eulogies and aims to establish their multifunctionality and the authorial elaboration by the preacher.